Description of Academic Learning Environment Undergraduate Nursing Study Program Faculty of Nursing Universitas Padjadjaran - Karisa, Putri; Fitria, Nita; Nurhakim, Furkon (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: A stressful, authoritarian, and lack of collaboration learning environment can reduce students' motivation and interest in learning which ends in learning outcomes that are not optimal. Efforts to improve the quality of the learning environment need to be done by assessing the learning process, teachers, academic achievement, learning atmosphere and social environment. The purpose of this study will be to identify the description of the academic learning environment.Method: This descriptive cross-sectional study was conducted on 271 participating students as a sample using the Dundee Ready Educational Environment Measure (DREEM). The sampling technique used is proportional stratified random sampling. The data were analyzed to determine the frequency distribution of the academic learning environment which was then analyzed for each sub-variable.Results: The results of this study show that the academic learning environment score is 133.75/200 (72%), included in more positive than negative category. Based on the sub dimensions, the results of the learning process (33.41/48), teachers (30.98/44), academic achievement (23.39/32), learning atmosphere (29.79/48), and social environment (16 ,17/28). Academic achievement is the sub dimension with the highest rating and social environment is the sub dimension with the lowest score.Conclusions: The assessment of the academic learning environment is included in the more positive than negative category, meaning that the implementation of nursing education has been going well even though there are deficiencies. DREEM will assess the parts that are already positive, need to be improved and need to be repaired.